1994
DOI: 10.2307/1602485
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Father after Divorce

Abstract: Fathers figure prominently in a child's postdivorce life whether they are involved or disinterested, but concerns about inadequate child support, noncustodial fathers who fail to visit, and the economic plight of single mothers have together raised policy questions about how better to enfranchise fathers with the rights and responsibilities of parenting and ensure them a continuing and meaningful role in the lives of their offspring. This article focuses on obstacles and avenues to ensuring a meaningful postdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
1
9
0
1
Order By: Relevance
“…While this avoidance is often indicative of children's grief and anger about their family, it may also simply be a response to change and an inability to predict family members' responses, especially new authority figures (Ferguson & Dickson, 1995;Thompson, McLanahan, & Curtin, 1992). Next to the stepparent-stepchild relationship, the restructuring of familial relationships is particularly pressing for fathers and children, because of fathers' often newfound role as noncustodial parents (Thompson, 1994) and perhaps because fathers in general are deemed to be less responsive to disclosures than mothers (Guerrero & Afifi, 1995a, 1995b. With this information in mind, the first hypotheses are set forth: H1: Children in first-marriage families have the least uncertainty about their family, followed by children in postdivorce single-parent families, and then stepfamilies.…”
Section: Adolescents' and Young Adults' Uncertainty And Avoidance Of mentioning
confidence: 99%
“…While this avoidance is often indicative of children's grief and anger about their family, it may also simply be a response to change and an inability to predict family members' responses, especially new authority figures (Ferguson & Dickson, 1995;Thompson, McLanahan, & Curtin, 1992). Next to the stepparent-stepchild relationship, the restructuring of familial relationships is particularly pressing for fathers and children, because of fathers' often newfound role as noncustodial parents (Thompson, 1994) and perhaps because fathers in general are deemed to be less responsive to disclosures than mothers (Guerrero & Afifi, 1995a, 1995b. With this information in mind, the first hypotheses are set forth: H1: Children in first-marriage families have the least uncertainty about their family, followed by children in postdivorce single-parent families, and then stepfamilies.…”
Section: Adolescents' and Young Adults' Uncertainty And Avoidance Of mentioning
confidence: 99%
“…First, in their groundbreaking Stanford Divorce Study, Maccoby and Mnookin (1992) found that in two thirds of cases where the father disagreed with the mother's request for sole custody, the father requesting joint custody was overruled by the judge and the mother was awarded sole custody. Second, as Thompson (1994) notes, “fathers who must negotiate with their wives over custody issues realize that, if their dispute comes to court, their chances of achieving a more generous custody settlement are remote at best” (p. 217). Third, Maccoby and Mnookin (1992) found that, even when mothers and fathers agreed on joint custody or on sole paternal custody, judges overruled these agreements in one‐quarter of such cases.…”
mentioning
confidence: 99%
“…Generally, nonresident fathering has been viewed as an impediment to father‐child relationships (e.g., Amato & Gilbreth; Fabricius & Hall, 2000). Most critically, opportunities for nurturance and involvement in children's lives clearly are fewer for nonresident fathers than for fathers in intact families (Finley; Thompson, 1994).…”
mentioning
confidence: 99%